Barriers and facilitators of evidence-based management of patients with bacterial infections among general dental practitioners: a theory-informed interview study. (December 2015) - Newlands, Rumana; Duncan, Eilidh; Prior, Maria; Elouafkaoui, Paula; Elders, Andrew; Young, Linda; Clarkson, Jan; Ramsay, Craig
Abstract Background General dental practitioners (GDPs) regularly prescribe antibiotics to manage dental infections although most infections can be treated successfully by local measures. Published guidance to support GDPs to make appropriate prescribing decisions exists but there continues to be wide variation in dental antibiotic prescribing. An interview study was conducted as part of the Reducing Antibiotic Prescribing in Dentistry (RAPiD) trial to understand the barriers and facilitators of using local measures instead of prescribing antibiotics to manage bacterial infections. Methods Thirty semi-structured one-to-one telephone interviews were conducted using the Theoretical Domains Framework (TDF). Responses were coded into domains of the TDF and sub-themes. Priority domains (high frequency: ≥50 % interviewees discussed) relevant to behaviour change were identified as targets for future intervention efforts and mapped onto 'intervention functions' of the Behaviour Change Wheel system. Results Five domains (behavioural regulation, social influences, reinforcement, environmental context and resources, and beliefs about consequences) with seven sub-themes were identified as targets for future intervention. All participants had knowledge about the evidence-based management of bacterial infections, but they reported difficulties in following this due to patient factors and time management. Lack of time was found to significantly influence their decision processes with regard to performing local measures. Beliefs about their capabilities to overcome patient influence, beliefs that performing local measures would impact on subsequent appointment times as well as there being no incentives for performing local measures were also featured. Though no knowledge or basic skills issues were identified, the participants suggested some continuous professional development programmes (e.g. time management, an overview of published guidance) to address some of the barriers. The domain results suggest a number of intervention functions through which future interventions could change GDPs' antibiotic prescribing for bacterial infections: imparting skills through training, providing an example for GDPs to imitate (i.e. modelling) or creating the expectation of a reward (i.e. incentivisation). Conclusions This is the first theoretically informed study to identify barriers and facilitators of evidence-based management of patients with bacterial infections among GDPs. A pragmatic approach is needed to address the modifiable barriers in future interventions intended to change dentists' inappropriate prescribing behaviour.